Natriuretic peptides enhance the oxidative capacity of human skeletal muscle - Stefan Engeli; Andreas L. Birkenfeld; Pierre-Marie Badin; Virginie Bourlier; Katie Louche; Nathalie Viguerie; Claire Thalamas; Emilie Montastier; Dominique Larrouy; Isabelle Harant; Isabelle de Glisezinski; Stefanie Lieske; et al. (The Journal of Clinical Investigation, 2012)
Cardiac natriuretic peptides (NP) are major activators of human fat cell lipolysis and have recently been shown to control brown fat thermogenesis. Here, we investigated the physiological role of NP on the oxidative metabolism of human skeletal muscle. NP receptor type A (NPRA) gene expression was positively correlated to mRNA levels of PPARγ coactivator-1α (PGC1A) and several oxidative phosphorylation (OXPHOS) genes in human skeletal muscle. Further, the expression of NPRA, PGC1A, and OXPHOS genes was coordinately upregulated in response to aerobic exercise training in human skeletal muscle. In human myotubes, NP induced PGC-1α and mitochondrial OXPHOS gene expression in a cyclic GMP–dependent manner. NP treatment increased OXPHOS protein expression, fat oxidation, and maximal respiration independent of substantial changes in mitochondrial proliferation and mass. Treatment of myotubes with NP recapitulated the effect of exercise training on muscle fat oxidative capacity in vivo. Collectively, these data show that activation of NP signaling in human skeletal muscle enhances mitochondrial oxidative metabolism and fat oxidation. We propose that NP could contribute to exercise training–induced improvement in skeletal muscle fat oxidative capacity in humans.